Investigating the response of different cell lines to the mixed radiation field produced of helium ion radiation - Ladan Rezaee (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd, 2019)
Introdution: A careful study of the physical and biological properties of helium ion radiation on the various cell lines is essential for the treatment planning. In this study, the biological response of several different cell lines has been investigated in 4He ions. Methods: Physical dose profiles and Linear Energy Transfer (LET) calculations were performed using the Monte Carlo Geant4 code. By studying the mixed radiation field, the biological effect of 4He primary ions, 3He and 6He secondary ions, as well as secondary proton, deuteron and triton are considered in calculations. Results: Biological doses and cell survival levels have been compared for these cell lines. The variation of relative biological effectiveness (RBE) for each cell line is calculated as a function of the phantom depth. The results have shown that the cell lines with the highest (α/β)ph levels have a higher sensitivity to damage cells against 4He radiation. Conclusion: Among the studied cell lines, the most appropriate treatment for 4He ion, the Colon adenocarcinoma cancer cell line has been selected. In addition, due to the large variation in RBE relative to the depth in the phantom, it is necessary to consider a variable RBE instead of a constant RBE.